2000
DOI: 10.1348/014466600164534
|View full text |Cite
|
Sign up to set email alerts
|

Attitude‐behaviour relations: The role of in‐group norms and mode of behavioural decision‐making

Abstract: Two experiments provided support for the central hypothesis--derived from social identity/self-categorization theories--that attitudes would be most likely to predict behaviour when they were supported by a congruent in-group norm. In the first experiment, norm congruency and mode of behavioural decision-making (spontaneous or deliberative) were orthogonally manipulated in a between-subjects study of career choice in psychology. Participants exposed to an attitudinally congruent in-group norm towards their pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 31 publications
(47 reference statements)
5
82
0
3
Order By: Relevance
“…In two tests of the theory of planned behavior, Terry and Hogg (1996) found that the perceived norms of a specific and relevant reference group were related to students' intentions to engage in health behaviors, but only for students who identified strongly with the group. In addition, these results have been replicated in a series of recent experimental studies (e.g., Terry, Hogg, & McKimmie, 2000;Wellen, Hogg, & Terry, 1998;White, Hogg, & Terry, 2002), providing more direct support for the social identity approach to attitude-behavior relations. The results of these studies have demonstrated that exposure to a group norm that is incongruent with one's attitude reduces the level of attitude-behavior consistency displayed, but only for individuals who identify strongly with the group.…”
Section: The Social Identity Approach To Attitude-behavior Relationsmentioning
confidence: 64%
“…In two tests of the theory of planned behavior, Terry and Hogg (1996) found that the perceived norms of a specific and relevant reference group were related to students' intentions to engage in health behaviors, but only for students who identified strongly with the group. In addition, these results have been replicated in a series of recent experimental studies (e.g., Terry, Hogg, & McKimmie, 2000;Wellen, Hogg, & Terry, 1998;White, Hogg, & Terry, 2002), providing more direct support for the social identity approach to attitude-behavior relations. The results of these studies have demonstrated that exposure to a group norm that is incongruent with one's attitude reduces the level of attitude-behavior consistency displayed, but only for individuals who identify strongly with the group.…”
Section: The Social Identity Approach To Attitude-behavior Relationsmentioning
confidence: 64%
“…Previous research has supported the social identity analysis of the role of norms in attitude-behaviour relations (e.g., Smith & Terry, 2003;Terry & Hogg, 1996;Terry, Hogg, & White, 1999;Terry, Hogg, & McKimmie, 2000;Wellen, Hogg, & Terry, 1998). In both field and laboratory research, normative support from a relevant and specific reference group, or exposure to a supportive group norm, has been found to increase the expression of attitude-consistent intentions and behaviour, while low levels of normative support, or exposure to an attitude-incongruent group norm, decreases the expression of attitudeconsistent intentions and behaviour, but only for individuals who identify strongly with the group (i.e., high identifiers).…”
Section: The Social Identity Approach To Attitude-behaviour Relationsmentioning
confidence: 89%
“…Indeed, previous studies (e.g. Terry, Hogg, & McKimmie, 2000) have shown that attitudes are most likely to predict behaviour when they are supported by a congruent ingroup norm, especially among high identifiers. The present results corroborate these findings.…”
Section: The Relationship Between Mcaa and Group-based Aggressionmentioning
confidence: 95%